(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Passive systems ventilation systems are gaining its popularity over mechanical ventilationsystems due to its inherent characteristics which help in reducing cost during operation, lowerrequirement of powerenergy as well as reduced emission of carbon dioxide. Various types ofventilation systems are available which utilizes solar energy and wind energy and as well as itscombination are also used. The present study gives the systematic review of the passive ventilationsystems for achieving indoor environment thermal comfort. Variety of passive systems which candeliver thermal comfort. Both experimental and CFD simulation both are rigorously utilized by theresearchers for analysis of various passive ventilation systems.CFD simulation ventilation systems aredevised by various researchers i.e. wind driven, solar driven and hybrid found to be an effective tool todesign earth -to-air heat exchanger (EAHE).It can be also conclude that hybrid systems which containssolar chimney, wind tower as well as underground systems can yield indoor environment.